Oral and dental health status in patients with chronic headache - Mohammad Samami; Fereshteh Najar-Karimi; Babak Bakhshayesh Eghbali; Aghil Hosseinpour Sanati; Afagh Hassanzadeh Rad (BMC, 2024)
Abstract Introduction Headache is an illness with high prevalence and adverse effects on quality of life. As oral or dental problems such as pain can trigger or aggravate it, we aimed to investigate and compare oral and dental health status in patients affected with chronic headaches and healthy individuals. Methods The present case-control study included 60 patients with chronic headaches (case) and 60 healthy individuals (control) in Rasht, Iran. The demographic characteristics and clinical examinations, including decayed/missing/filled teeth (DMF-T) and community periodontal index of treatment needs (CPITN) indices, as well as bruxism, frequency of tooth brushing and flossing, and maxillary and mandibular tooth wear were recorded in a checklist. Data analysis was performed using the IBM SPSS version 28 at a significance level of 0.05. Results The case group consisted of 25 men (41.7%) and 35 women (58.3%) with an average age of 32.55 ± 6.62 years, while the control group had 27 men (45%) and 33 women (55%) with an average age of 30.95 ± 6.33 years. The study groups were not significantly different in bruxism, frequency of tooth brushing and flossing, DMFT, CPTIN, and maxillary and mandibular tooth wear. Conclusion It seems that chronic headaches do not significantly affect the oral and dental health of the sufferers. Moreover, it appears that these patients are well aware of the role of oral and dental hygiene in triggering or aggravating the episodes of headaches.